Equilíbrio térmico e emissão de metano em vacas Jersey - Carvalho, Marcos Davi de [UNESP] (2015)
The present work aimed to study the physiological variables and enteric methane emission in Jersey breed dairy cow, relating with environmental variables. To understand the dynamics of thermal equilibrium was conducted an experiment where we used twelve animals of Jersey breed lactating cow with average daily production of 17.7 L/day, by the herd of APTA of Ribeirão Preto, the average of 362.3 ± 31.0, not pregnant and with an average of two months of lactation. An experiment was conducted adopting an experimental Latin square design where 12 animals were evaluated during 12 days of data collection and being observed for 12 hours long. The skin surface temperature was strongly correlated with the environmental meteorological variables (temperature and relative humidity), and its coefficient of correlation was equal to 0.69, -0.50 and weakly correlated to the solar radiation -0.11. The lowest average of rectal temperature was 38.5 ± 0.33 ° C and the highest was 40.3 ± 0.05 ° C. The coat surface temperature increased until around 16:00 hours, and after that it began to decrease, while the epidermis had a decrease starting from 18:00 hours. The temperature of the epidermis showed a positive correlation with the hair coat temperature of 0.83 and with the rectal temperature of 0.55.The respiratory frequency showed a positive correlation with the air temperature, 0.35. The heat loss by respiratory evaporation showed a positive correlation with the air temperature, 0.71. So that, the high average, was at 13 hours 30.4±0.33, W m-2 and the low, around at 8 hours, with average of 12.6 ± 0.29 W m-2 while their correlation with relative humidity was -0,51. The hour and day effects was significant (P <0.01) for metabolic heat production and enteric methane emission. The correlation among methane emission and metabolic heat production was of 0.23. The analysis of variance showed that collet day, hour of class and animal were significant ...